2018
DOI: 10.1071/hc17072
|View full text |Cite
|
Sign up to set email alerts
|

From diagnosis to long-term management: the experiences of older New Zealanders with obstructive sleep apnoea

Abstract: INTRODUCTION In New Zealand (NZ), access to public sleep services is limited to people deemed with the highest need. The prevalence of obstructive sleep apnoea (OSA) increases with age, but the symptoms and the treatment pathway is expected to differ for older compared to younger patients. This study explored the experience of older people regarding diagnosis and treatment services for OSA in order to inform considerations required in primary health and sleep services. METHODS Patients who were initiated on Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…This knowledge comes mainly from the perspective of adult patients with COPD, pulmonary fibrosis, and OSA receiving CPAP and from their carers. These studies were conducted in five countries (three from Europe) [45,46,47,48,49,50,51,52,53]. Thus, this evidence may not completely apply to the experience of younger patients (including children) and that of their carers or to patients with other diseases and other treatment modalities (e.g., Bilevel Positive Pressure Airway, LTOT) and from other countries/continents.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This knowledge comes mainly from the perspective of adult patients with COPD, pulmonary fibrosis, and OSA receiving CPAP and from their carers. These studies were conducted in five countries (three from Europe) [45,46,47,48,49,50,51,52,53]. Thus, this evidence may not completely apply to the experience of younger patients (including children) and that of their carers or to patients with other diseases and other treatment modalities (e.g., Bilevel Positive Pressure Airway, LTOT) and from other countries/continents.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies explored the patient’s experience with LTOT [45,46], and the others assessed the patient’s experience with non-invasive ventilation [47,48,49,50,51]. These studies were conducted in the United States of America [45,47], New Zealand [48,49], the United Kingdom [50], Sweden [51], and Spain [46] and included both adult patients and carers. Two reviews were also found on the needs of patients with COPD and were also used in the present analysis [52,53].…”
Section: Patient Experience In the Context Of Hrtmentioning
confidence: 99%
See 3 more Smart Citations